2011
DOI: 10.1016/j.bbr.2011.07.046
|View full text |Cite
|
Sign up to set email alerts
|

Long-term ovariectomy alters social and anxious behaviors in semi-free ranging Japanese macaques

Abstract: Symptoms of anxiety and depression often occur in young women after complete hysterectomy and in older women during menopause. There are many variables that are hard to control in human population studies, but that are absent to a large extent in stable nonhuman primate troops. However, macaques exhibit depressive and anxious behaviors in response to similar situations as humans such as isolation, stress, instability or aggression. Therefore, we hypothesized that examination of behavior in ovariectomized indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 42 publications
(47 reference statements)
1
35
0
Order By: Relevance
“…However, the trend toward Intact animals having higher CRF fibers in the dorsal raphe than the Ovx group is the opposite of earlier data. Although the ranks of the individuals did not change, the Intact individuals participated in sexual behavior to a significantly greater extent than the Ovx individuals (Coleman et al, 2011). There is an increase in fighting in the troop during mating season that would have involved the Intact animals to a much larger extent than the Ovx animals.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…However, the trend toward Intact animals having higher CRF fibers in the dorsal raphe than the Ovx group is the opposite of earlier data. Although the ranks of the individuals did not change, the Intact individuals participated in sexual behavior to a significantly greater extent than the Ovx individuals (Coleman et al, 2011). There is an increase in fighting in the troop during mating season that would have involved the Intact animals to a much larger extent than the Ovx animals.…”
Section: Discussionmentioning
confidence: 82%
“…There were subtle differences between the regulation of serotonin-related genes by hormone replacement in the short-term Ovx monkeys compared to the differences in expression observed in the Intact versus long-term Ovx monkeys, again possibly related to the loss of serotonin neurons in the latter. We also reported that the same Ovx monkeys exhibited a decrease in positive social behavior in the troop and exhibited an increase in certain anxiety-related behaviors in temperament tests (Coleman et al, 2011). …”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, unwanted side-effects of hormone-mediated contraceptives such as diabetes mellitus, Cushing’s diseases, osteoporosis, weight gain, increased aggression, as well as suppression of oestrus and proceptive behavior might develop among individuals [Glatston, 1998]. Permanent sterilization has also been associated with negative effects on social behavior and anxiety in macaques [Colemana et al, 2011]. The use of contraceptive vaccines developed for wildlife in monkeys is also controversial as the adjuvants currently used caused skin lesions and infections and the duration of contraception is variable [Dascanio et al, 2014].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that ovariectomized Japanese macaques (Macaca fuscata Blyth, 1875) exhibited a significant decrease in positive social behavior (Coleman et al 2011). In contrast, systemic estradiol-priming significantly increased time spent in social interaction with a conspecific in rats (Frye et al 2008).…”
Section: Effects Of Ovariectomy On Female Mandarin Volesmentioning
confidence: 95%